2014
DOI: 10.1111/pme.12498
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Incidence of Severe Pain Events Following Surgery: A Review of 333,000 Pain Scores

Abstract: Objective/Background Prior work has not addressed sex differences in the incidence of severe postoperative pain episodes. The goal of this study was to examine sex differences in clinical postoperative pain scores across an array of surgical procedures using direct comparisons of numeric rating scale pain scores as well as using the incidence of severe pain events (SPEs). Design/Setting Retrospective cohort study of over 300,000 clinical pain score observations recorded from adult patients undergoing nonambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 45 publications
4
32
3
Order By: Relevance
“…In the whole-model analysis, male patients had a substantially more rapid decrease in postoperative pain compared with female patients, even after controlling for age, comorbidity status, type of surgery, and surgical complexity. These findings extend prior work on sex differences in static pain scores in both experimental and clinical settings [4,16,21,31,35]. However, in age-stratified analyses, the effect of sex on postoperative pain was significant only in those greater than or equal to 65 years of age.…”
Section: Discussionsupporting
confidence: 84%
“…In the whole-model analysis, male patients had a substantially more rapid decrease in postoperative pain compared with female patients, even after controlling for age, comorbidity status, type of surgery, and surgical complexity. These findings extend prior work on sex differences in static pain scores in both experimental and clinical settings [4,16,21,31,35]. However, in age-stratified analyses, the effect of sex on postoperative pain was significant only in those greater than or equal to 65 years of age.…”
Section: Discussionsupporting
confidence: 84%
“…The SPTS-12 also demonstrated good to excellent internal consistency for both men and women in Studies 2 and 3. However, due to the small number of women in the study, this result should be interpreted tentatively especially in light of the almost ubiquitous findings that women and men differ in terms of their responses to acute experimental,47,59 clinical,60 and chronic pain 61. Reliability within subgroups such as sex should be examined in future studies with larger samples from various settings.…”
Section: Discussionmentioning
confidence: 89%
“…However, more recently published data investigating procedure-specific risk factors for the development of severe POP strongly support a role of sex—apart from preoperative chronic pain and age—as one major predictor [12]. Another recent large retrospective study confirmed this by showing a higher risk of females to report more severe pain events; however sex differences were somehow small with odds ratios between 1.14 and 1.16 [22]. Here, we demonstrate that sex is as well a predictor for worst POP since surgery similar to those earlier clinical trials showing an effect on POP [79, 12, 22].…”
Section: Discussionmentioning
confidence: 99%